A Stability Control Method to Maintain Synchronization Stability of Wind Generation under Weak Grid - Minhai Wu; Jun Zeng; Gengning Ying; Jidong Xu; Shuangfei Yang; Yuebin Zhou; Junfeng Liu (Energies, 2024)
When wind generation systems operate under weak grid conditions, synchronization stability issues may arise, restricting the wind farms’ power transfer capacity. This paper aims to address these challenges on the grid side. Firstly, a clear exposition of the coupling mechanism between the grid-connected inverters (GCI) of wind generations and the weak grid is provided. Then, an equivalent parallel compensation method integrated into the PLL to enhance synchronization stability is proposed. The method changes the reference of the PLL and equivalently parallels the virtual resistance with the grid impedance, which alters the strength of the grid. It reshapes the inverter qq-axis impedance at the impedance level. And the proper design of the virtual resistance will enhance the system’s stability without compromising the dynamic performance of PLL. In addition, the proposed method is robust to the parameter changes of the grid-connected system and the grid impedance measurement error. Experimental results are presented to validate the effectiveness of the compensation method.